(untitled) (Research, Society and Development, 2022)
The great growth of Food and Nutrition Units (UAN’s) is associated with a large food consumption and the waste of natural resources and food. In this way, the study aimed to analyze the waste of food by the diners of the hospital restaurant, and their knowledge about sustainable practices, during the period of validity at HUAC in the city of Campina Grande-PB. The study was exploratory and quantitative, carrying out the application of a questionnaire regarding sustainable practices. A percentage stood out where 70.6% of respondents said they do not waste food and 81.4% reported that they only put on their plate what they are going to consume, however, during the analysis of the meals served, it was found after the distribution of the per capita, a waste of 18.7% in the FNU, however the literature accepts a maximum of 10%. Satisfactory results were obtained regarding questions about the environment: 55% claimed to be very interested in the topic, 30.3% reasonably interested, and only 2.9% have no knowledge, 86.3% support teaching about sustainability in schools; and the use of sustainable practices such as full use of food was 64.7%; however, 16.7% never consumed food using this technique, 12.7% did not know if they had already consumed it. The use of disposable cups presented 40.2%, in contrast, 22.5% denied their use, 36.3% said they used them in some situations. It is concluded that it is of great importance to emphasize the implementation of educational actions in order to alleviate this food waste, reduce hospital costs and impacts on the environment.